Unusual Ventilatory Response to Exercise in Patient with Arnold-Chiari Type 1 Malformation after Posterior Fossa Decompression - Keely Smith; Ana M. Gomez-Rubio; Tomika S. Harris; Lauren E. Brooks; Ricardo A. Mosquera (Case Reports in Pediatrics)
We present a case of a 17-year-old Hispanic male with Arnold-Chiari Type 1 [AC-Type 1] with syringomyelia, status post decompression, who complains of exercise intolerance, headaches, and fatigue with exertion. The patient was found to have diurnal hypercapnia and nocturnal alveolar hypoventilation. Cardiopulmonary testing revealed blunting of the ventilatory response to the rise in carbon dioxide (CO2) resulting in failure of the parallel correlation between increased CO2 levels and ventilation; the expected vertical relationship between PETCO2 and minute ventilation during exercise was replaced with an almost horizontal relationship. No new pathology of the brainstem was discovered by MRI or neurological evaluation to explain this phenomenon. The patient was placed on continuous noninvasive open ventilation (NIOV) during the day and CPAP at night for a period of 6 months. His pCO2 level decreased to normal limits and his symptoms improved; specifically, he experienced less headaches and fatigue during exercise. In this report, we describe the abnormal response to exercise that patients with AC-Type 1 could potentially experience, even after decompression, characterized by the impairment of ventilator response to hypercapnia during exertion, reflecting a complete loss of chemical influence on breathing with no evidence of abnormality in the corticospinal pathway.